RANCANG BANGUN KONTROL DAN MONITORING BEBAN SATU FASA BERBASIS ANDROID DENGAN SENDOR PZEM-004T - Asry Nathania Ardelia Sihite; Catra Indra Cahyadi; Suherman Suherman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The development of Internet of Things (IoT) technology has driven progress in electrical device monitoring and control systems, especially in single-phase installations. This research aims to design and implement an Android-based single-phase electrical load monitoring and control system by utilizing the PZEM-004T sensor to measure voltage, current, and power in real-time. This system uses two microcontrollers, namely Arduino Nano as the main processor of sensor data and ESP32 to send data to the Blynk application via a WiFi connection. The Blynk application serves as a user interface, enabling remote monitoring and control of electrical loads through a smartphone. Three PZEM-004T sensors are used to monitor three separate load channels, while a 4-channel relay module acts as an actuator to control the ON/OFF status of each load. The system was tested under various load conditions to verify the accuracy of the sensor readings and the responsiveness of control commands via Blynk. This system is not only effective for monitoring and controlling power usage efficiently, but it also holds great potential as a learning tool in the fields of electronics and IoT-based electrical system applications for residential or laboratory environments. Keywords: Internet of Things, ESP32, PZEM-004T, Load Monitoring, Power Control Abstrak: Perkembangan teknologi Internet of Things (IoT) telah mendorong kemajuan dalam sistem monitoring dan kontrol perangkat listrik, terutama pada instalasi satu fasa. Penelitian ini bertujuan merancang dan mengimplementasikan sistem monitoring dan kontrol beban listrik satu fasa berbasis Android dengan memanfaatkan sensor PZEM-004T untuk mengukur tegangan, arus, dan daya secara real-time. Sistem ini menggunakan dua mikrokontroler, yaitu Arduino Nano sebagai pengolah utama data sensor dan ESP32 untuk mengirimkan data ke aplikasi Blynk melalui koneksi WiFi. Aplikasi Blynk digunakan sebagai antarmuka pengguna yang memungkinkan monitoring data dan pengendalian beban secara jarak jauh melalui smartphone. Tiga sensor PZEM-004T digunakan untuk memantau tiga saluran beban yang berbeda, sedangkan modul relay 4 channel digunakan sebagai aktuator yang mengontrol status hidup atau mati masing-masing beban. Sistem diuji dengan berbagai variasi kondisi beban untuk memastikan keakuratan pembacaan sensor dan kecepatan respon kontrol melalui Blynk. Sistem ini tidak hanya efektif untuk mengontrol dan memantau penggunaan energi listrik secara efisien, tetapi juga sangat potensial untuk digunakan sebagai media pembelajaran dalam bidang elektronika dan pemanfaatan teknologi IoT pada instalasi listrik rumah tangga atau laboratorium. Kata kunci: Internet of Things, ESP32, PZEM-004T, Monitoring Beban, Kontrol Daya